Exploring the factors affecting the purchase decisions of customers in online marketing in Bangladesh - Niloy, Abid Hasan (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.